2017
DOI: 10.1016/j.molp.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Functional Accumulation of Antenna Proteins in Chlorophyll b-Less Mutants of Chlamydomonas reinhardtii

Abstract: The green alga Chlamydomonas reinhardtii contains several light-harvesting chlorophyll a/b complexes (LHC): four major LHCIIs, two minor LHCIIs, and nine LHCIs. We characterized three chlorophyll b-less mutants to assess the effect of chlorophyll b deficiency on the function, assembly, and stability of these chlorophyll a/b binding proteins. We identified point mutations in two mutants that inactivate the CAO gene responsible for chlorophyll a to chlorophyll b conversion. All LHCIIs accumulated to wild-type le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…These mutants are photosensitive, severely chlorotic, and/or yellow in the dark (Li and Timko, 1996;Chekounova et al, 2001;Falciatore et al, 2005;von Gromoff et al, 2008;Meinecke et al, 2010;Grovenstein et al, 2013). It was recently demonstrated that the specific loss of chlorophyll b in Chlamydomonas does not disrupt accumulation of LHCI and LHCII polypeptides as long as chlorophyll a biosynthesis remains intact (Bujaldon et al, 2017). Despite the phenotypic discrepancies among these mutants, our transcriptomic data suggest that aberrant accumulation of PSI, LHCI, and LHCII polypeptides in the hmox1 mutant is not due to inhibition of chlorophyll biosynthesis-related gene expression.…”
Section: Phenotypic Similarities Of Chlorophyll Biosynthesis Mutants mentioning
confidence: 99%
“…These mutants are photosensitive, severely chlorotic, and/or yellow in the dark (Li and Timko, 1996;Chekounova et al, 2001;Falciatore et al, 2005;von Gromoff et al, 2008;Meinecke et al, 2010;Grovenstein et al, 2013). It was recently demonstrated that the specific loss of chlorophyll b in Chlamydomonas does not disrupt accumulation of LHCI and LHCII polypeptides as long as chlorophyll a biosynthesis remains intact (Bujaldon et al, 2017). Despite the phenotypic discrepancies among these mutants, our transcriptomic data suggest that aberrant accumulation of PSI, LHCI, and LHCII polypeptides in the hmox1 mutant is not due to inhibition of chlorophyll biosynthesis-related gene expression.…”
Section: Phenotypic Similarities Of Chlorophyll Biosynthesis Mutants mentioning
confidence: 99%
“…Defects in Chl biosynthesis or its regulation can have severe impacts on the amounts of photosystem‐ or LHC proteins as well as their structure and the resulting light energy transfer within the photosynthetic apparatus (e.g. Moseley et al ., ; Formighieri et al ., ; Bujaldon et al ., ). In strain ami CYG12 , 77K Chl fluorescence spectra showed an increased and slightly blue‐shifted emission maximum for PSI/LHCI (Figure ), which might be indicative of uncoupled LHCI antennae (Moseley et al ., ; Wlodarczyk et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…73.4% pairwise identity with Chlamydomonas eustigma ). We did, however, uncover two other duplicated genes: GENOMES UNCOUPLED ( GUN4 ), encoding a regulatory subunit of Mg‐chelatase that enhances chlorophyll biosynthesis and contributes to retrograde signalling (Formighieri et al ., ; Brzezowski et al ., ), and chlorophyllide a oxygenase ( CAO ), which is responsible for the production of chl b (Tanaka et al ., ; Bujaldon et al ., ). To the best of our knowledge, this is the first report of duplication of these genes in a green alga.…”
Section: A Dpor‐less Chlamydomonasmentioning
confidence: 97%